Fire behavior of upholstered furniture and mattresses - Krasny, John (Noyes Publications ; William Andrew Pub., 2001)
The flammability of upholstered furniture is a major concern to engineers and others across a wide swath of organizations. This book was written to provide its audience with the science and engineering needed to better understand the combustibility of the products they manufacture, purchase, and try to extinguish. It addresses the science and engineering information needs of public and private sector fire technology personnel, including fire service students and officers, fire investigators, fire protection engineers, government officials; textile, chemical, and furniture industry personnel, or institutional furniture purchasers.